The adoption and impact of engineering-type measures to address climate change: evidence from the major grain-producing areas in China - Song, C.; Liu, R.; Oxley, Leslie; Ma, H. (Blackwell Publishing Asia, 2018)
© 2018 Australasian Agricultural and Resource Economics Society Inc. Employing an endogenous switching regression model, we investigate the drivers underlying the adaptations made by farm households and their impacts on crop net incomes for adopters and nonadopters, based on a large panel survey data set across the major grain-producing provinces in China. The results show that: (i) access to public climate information and technical or physical support increases the likelihood that farmers adapt to climate change by undertaking irrigation and/or drainage measures; and (ii) decisions to adapt increased crop yield, but they did not significantly increase crop profit margins. This point appears to have been ignored by previous studies. Based on these new empirical results, the paper suggests that government should continue to provide climate information and various types of supports to improve farmers’ adaptation abilities and help to reduce the levels of factor input by, for example, substituting organic for chemical fertiliser inputs. Such government-led policies should be supported alongside the implementation of domestic agricultural supply-side reform.